Group image concerns - Arno Apffelstaedt; Gönül Dogan; Fabian Hoffmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We introduce a novel concept, group image concerns, showing that individuals change their behavior and are willing to incur personal costs to cultivate a positive image of their groups. We develop an experimental method to identify and quantify group image concerns, and conduct a series of laboratory and online experiments to measure them in three distinct domains. In the first two experiments focused on charitable behavior, participants donate more when their contributions are publicly associated with their group, despite their individual identity remaining private. They also pay significant amounts to keep low donations from other group members private and to make high donations public. These findings emerge for students in the laboratory, using university affiliation as their group identity, as well as for online participants from the general U.S. population, using religious affiliation as their group identity. Additional online experiments explore group image concerns among Democrats and Republicans regarding their group's knowledge of the U.S. national anthem, as a measure of patriotism, and among U.S. students concerning their university's reputation for intelligence in solving matrix completion tasks. We isolate group image concerns from individual image concerns and benchmark them against individual image concerns in our laboratory experiment. Our results establish group image concerns as an important driver of individual behavior and a significant source of utility across various domains.
Keywords: D01; D91; C92; 330; social identity and behavior; group image concerns; experiments; charitable and prosocial behavior; intelligence; political identity; religious identity; real effort